The Influence of Work-Life Balance, Workload, and Work Stress on Turnover Intention of Generation Z Employees PT. Ruifeng Hande Indonesia - Rita Susilawati; Indriani Indriani; Dharliana Ayu Hardjowikarto; Sunimah Sunimah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to examine how work-life balance, workload, and job stress affect turnover intention among Generation Z employees at PT Ruifeng Hande Indonesia. Generation Z is known to have high expectations of work-life balance, but is also more vulnerable to work stress and pressure, which can increase their intention to change jobs. The research method used is quantitative with a multiple linear regression approach. The results showed that work stress has a significant effect on turnover intention, while work-life balance and workload do not have a significant effect. This finding indicates that job stress is the main factor that drives Generation Z to leave the company, while work-life balance and workload may be influenced by other factors such as job satisfaction or compensation. The results of this study have an important impact on company management in designing policies that can improve employee welfare and reduce turnover. One way to do this is by creating a more flexible work environment and managing workload more effectively.